Predictors of Medication Adherence in Pediatric Inflammatory Bowel Disease Patients at the Stollery Children’s Hospital - L Kitney; JM Turner; D Spady; B Malik; W El-Matary; R Persad; HQ Huynh (Canadian Journal of Gastroenterology)
BACKGROUND: Patients with inflammatory bowel disease (IBD) often do not take their medications as prescribed.